Pengadaan Fasilitas Sarana Air Bersih di Dusun Juma Kancil Desa Onan Lama Kecamatan Pegagan Hilir Kabupaten Dairi - S, Ewin Handoco; Barat, Welmar Olfan Basten; Naibaho, Winfronstein; Nur Jannah Ginting (CERED Indonesia Publishing, 2024)
Procurement of Clean Water Facilities in Juma Kancil Hamlet, Onan Lama Village, Pegagan Hilir District, Dairi Regency, where clean water is one of the community needs that supports the life of a community. The provision of clean water is closely related to the cleanliness and health status of every individual in society. Procurement of Clean Water Facilities in Juma Kancil Hamlet, Onan Lama Village, Pegagan Hilir District to provide clean water facilities and infrastructure in everyday life. The purpose of this activity is to provide clean water facilities for local communities to be able to use clean water in their daily activities. The people of Onan Lama Village, Juma Kancil Hamlet really need a real touch to be able to receive direct benefits from the existence of clean water facilities in the location where they live. So far, people have had to walk long distances from the top of the hill to the valley or their neighboring villages which are around 3-3.5 kilometers from their village and have not been touched by the construction of clean water facilities for hundreds of years. So this is very burdensome and not effective and efficient in terms of time, energy and costs. So with this development it is hoped that there will be direct action to the community. So the community really needs the construction of clean water facilities.